KEANEKARAGAMAN TUMBUHAN DI KAWASAN PELESTARIAN PLASMA NUTFAH PT SURYA HUTANI JAYA PROVINSI KALIMANTAN TIMUR - Sodikin, Diki Mohamad (Faculty of Forestry and Environment, Universitas Kuningan, 2023)
The Germplasm Conservation Area (KPPN) is part of the area designated for conservation purposes. This area is an area that is fragmented by Plantation Forest, Mining and Plantation activities. The aim of this research is to determine the composition and diversity of plants in the protected area of KPPN PT Surya Hutani Jaya. The sampling method used was purposive sampling. The results of this research show that the diversity of vegetation types in the PT Surya Hutani Jaya Germplasm Conservation Area at 4 habitus levels is known to have no striking or dominating vegetation at all vegetation levels in large numbers and evenly distributed throughout the area, this shows the diversity of vegetation types in the area in even condition. The level of diversity of vegetation types at the seedling, sapling and pole level is included in the high criteria, while the level of diversity at the tree level is included in the medium criteria based on the Senon H' index value. This shows that the stability of the ecosystem is almost even with a fairly high diversity of species both at the seedling, stake and tree levelKawasan Pelestarian Plasma Nutfah (KPPN) merupakan bagian kawasan yang diperuntukkan untuk kepentingan konservasi. Kawasan tersebut merupakan kawasan yang terfragmentasi oleh kegiatan Hutan Tanaman, Pertambangan dan Perkebunan. Tujuan penelitian ini adalah untuk mengetahui komposisi dan keanekaragaman tumbuhan di kawasan lindung KPPN PT Surya Hutani Jaya Pengambilan sampling yang digunakan adalah menggunakan metode purposive sampling. Hasil penelitian ini menunjukan bahwa keanekaragaman jenis vegetasi di Kawasan Pelestarian Plasma Nutfah PT Surya Hutani Jaya pada 4 tingkat habitus diketahui tidak ada vegetasi yang mencolok atau mendominasi pada selutuh tingkat vegetasi dengan jumlah yang besar dan merata diseluruh areal, hal tersebut menunjukan keanekaragaman jenis vegetasi dikawasan tersebut dalam kondisi merata. Tingkat keanekaragaman jenis vegetasi pada tingkat semai, pancang dan tiang termasuk dalam kriterium tinggi sedangkan tingkat keanekaragaman pada tingkat pohon termasuk dalam kriterium sedang berdasarkan nilai indeks senon H’. Hal tersebut menunjukan stabilitas ekosistem yang hamper merata dengan keragaman jenis yang cukup tinggi baik di tingkat semai, pancang tiang dan pohon